Biblical terror why law and restoration in the Bible depend upon fear - Cataldo, Jeremiah W.; Bloomsbury (London New York Oxford New Dehli Sydney T&T Clark, 2017)
"Law and restoration are central concepts in the Bible, but they were not always so. To trace out the formation of those biblical concepts as elements in defensive strategies, Cataldo uses as conversational starting points theories from Zizek, Foucault and Deleuze, all of whom emphasize relation and difference. This work argues that the more modern assumption that biblical authors wrote their texts presupposing a central importance for those concepts is backwards. On the contrary, law and restoration were made central only through and after the writing of the biblical texts - in particular, those that were concerned with protecting the community from threats to its identity as the "remnant". Modern Bible readers, Cataldo argues, must renegotiate how they understand law and restoration and come to terms with them as concepts that emerged out of more selfish concerns of a community on the margins of imperial political power." --
Introduction -- The problems of revelation, ritualization, contradiction, and law's dependence upon them -- Restoration in Haggai-Zechariah as dependent upon difference -- The role of exclusion in monotheistic law -- Constructivism as a consequence of exile -- Differentiating exiles -- Returning to the centrality of religion
Includes bibliographical references (pages 241-251) and indexes
Keywords: Žižek, Slavoj; Deleuze, Gilles -- 1925-1995; Foucault, Michel -- 1926-1984; Žižek, Slavoj; Deleuze, Gilles 1925-1995; Foucault, Michel 1926-1984; Bible -- Social scientific criticism; Bible -- Psychology; Bible -- Social scientific criticism; Bible -- Psychology; Fear -- Biblical teaching; Law (Theology) -- Biblical teaching; Jews -- Restoration -- Biblical teaching; Jewish Law